Emmy and the incredible shrinking rat - Jonell, Lynne; Bean, Jonathan, 1979- (New York : H. Holt, 2007)
When Emmy discovers that she and her formerly loving parents are being drugged by their evil nanny with rodent potions that can change people in frightening ways, she and some new friends must try everything possible to return things to normal.
M
b
b
Keywords: Rodents -- Juvenile fiction; Rodents -- Fiction; Humorous stories; Humorous fiction